Seleksi Generasi Bersegregasi pada Galur-Galur Padi untuk Sawah Tadah Hujan - WAGE R. ROHAENI; UNTUNG SUSANTO (Agrotrop : Journal on Agriculture Science, 2014)
Selection on Segregating Generation of Paddy Lines for Rainfed. High yielding variety of paddy adapted for rainfed is not many developed until now. Just Inpari 38 that has been released successfully for rainfed areal. Segregating population is the basic for breeding activity. Indonesian Centre of Rice Research has been creating based population for creating new varieties adapted on ranfed environment. The aim of this research was for getting promising lines adapted on rainfed with good vigor, resistence form host and pest, and early maturity. This research was done at wet season in 2014 (November 2014 – March 2015) in rainfed areal, Margasari, Pasawahan district-Purwakarta, West Java. About 2694 lines were evaluated as genetic material. Bulk and Pedigree methods was being used on this research. The selection activity has done successfully with getting 637 best lines that has good score of vigorous (score 1 and 3) and healthy. There were consist of 21.19% from early generation, 63.26% from middle generation, and 19.47% from advanced generation. About 203 lines has early maturity criteria and 434 lines has medium maturity criteria.